Criticism of Classical Arabic Prose Discourse (Its Development and Critical Works) - benmessahel, bayal (El Omda in Linguistics and Discourse Analysis, 2023)
Some of the old reviewers have realized that the criticism of prose discourse among the Arabs needs to be resumed in consideration and assessment. They have recognized the ill luck of prose discourse in our critical heritage ,for that they felt that the ancient Arabic prose has lacked attention and focus compared to the fortune of poetic discourse, so they tried to redress this omission and deficiency by allocating Independent literatures for the study of criticism, and theorizing of prose, and perhaps the most prominent of those critics who represented the written stage of prose criticism are : Ibn Qutaybah al-Dinuri, Ibn al-Modabar, Ibn Abd al-Ghafoor al-Kalayi and others, who were the subject of this research, while identifying stage of narrative criticism that preceded them.